Paradigma Integrasi Maqasid dan Huda Al-Qur’an - Muhammad Hariyadi; Aldomi Putra; Aas Siti Sholichah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The Integration Paradigm of Maqasid and Huda Al-Qur'anThis article aims to reveal the theory of maqasid al-Qur'an and huda al-Qur'an which is currently a trending topic in the study of al-Qur'an science in order to reveal the goals and instructions of Allah SWT in the verses of al-Qur'an. Qur'an. The study of maqasid and huda al-Qur'an is like two different things, so it requires research to answer this question. This research is a qualitative research with the type of library research which refers to books and journals whose discussion is related to maqasid and huda al-Qur'an, through an ontological, epistemological and axiological approach that will give birth to an integration paradigm. The author finds that substantially the two theories do not have significant differences in all scientific approaches, it is even revealed that both have similarities in terms of discussion, scope, and goals in revealing the goals and instructions contained in the verses of the Qur'an. Even if there is a difference, then scientifically the difference is considered insignificant, because it only lies in the bearer of the theory and religious ideology as the background